Pullulan Films with PCMs: Recyclable Bio-Based Films with Thermal Management Functionality - Kizildag, Nuray (Mdpi, 2023)
The use of phase-changing materials (PCMs) is a practical and powerful way of buffering thermal fluctuations and maintaining the isothermal nature of the storage process. In this study, melamine formaldehyde microcapsules with paraffin cores were used as PCMs; pullulan films with PCMs were prepared by the film-casting method; and the composite films prepared were analysed with regard to their chemical structure, thermal properties, thermal stability, and recyclability. Uniform films displaying thermal management functionality were prepared. The amount of 75 wt.% PCM were added to the pullulan film structure which enabled the preparation of a composite film that displayed 104.85 J g(-1) of heat storage during heating and 103.58 J g(-1) of heat release during cooling. Multiple heating and cooling cycles showed that the composite films maintained their thermal management functionality after multiple heating-cooling cycles. The PCMs could be recovered with a yield of approximately 95% by the application of a simple dissolution and filtration process. The morphology, chemical structure, and thermal properties of the PCMs were maintained after the recovery process. The bio-based composite films with thermal management functionality and recyclability are proposed as an innovative, practical, and effective system for thermoactive storage and packaging applications.
Keywords: bio-based; encapsulated PCMs; packaging films; phase-changing materials; pullulan; recyclable; thermal management; thermoactive; thermoregulation